Neural Stem Cells Overexpressing Nerve Growth Factor Improve Functional Recovery in Rats Following Spinal Cord Injury via Modulating Microenvironment and Enhancing Endogenous Neurogenesis - Wang, Lei; Gu, Sujie; Gan, Jinlu; Tian, Yi; Zhang, Fangcheng; Zhao, Hongyang; Lei, Deqiang (Frontiers in Cellular Neuroscience, 2021)
Spinal cord injury (SCI) is a devasting event characterized by severe motor, sensory and autonomic dysfunction. Currently, there is no effective treatment. Previous studies showed neural growth factor (NGF) administration was a potential treatment for SCI. However, its targeted delivery is still challenging. In this study, neural stem cells (NSCs) were genetically modified to overexpress NGF, and we evaluated its therapeutic value following SCI. Four weeks after transplantation, we observed that NGF-NSCs significantly enhanced the motor function of hindlimbs after SCI and alleviated histopathological damage at the lesion epicenter. Notably, the survival NGF-NSCs at lesion core maintained high levels of NGF. Further immunochemical assays demonstrated the graft of NGF-NSCs modulated the microenvironment around lesion core via reduction of oligodendrocyte loss, attenuation of astrocytosis and demyelination, preservation of neurons, and increasing expression of multiple growth factors. More importantly, NGF-NSCs seemed to crosstalk with and activate resident NSCs, and high levels of NGF activated TrkA, upregulated cAMP-response element binding protein (CREB) and microRNA-132 around the lesion center. Taken together, the transplantation of NGF-NSCs in the subacute stage of traumatic SCI can facilitate functional recovery by modulating the microenvironment and enhancing endogenous neurogenesis in rats. And its neuroprotective effect may be mediated by activating TrkA, up-regulation of CREB and microRNA-132.